Characterisation of carnotite and tyuyamunite using Raman, luminescence and laser-induced breakdown spectroscopy. (December 2022) - Frankland, Victoria L.; Milodowski, Antoni E.; Read, David
Abstract: Among the wide range of natural uranium minerals, uranyl vanadates have attracted particular attention due to the economic viability of co-producing uranium and vanadium for industrial applications The typically remote locations of the ore deposits favour in situ analytical techniques offering rapid, minimally destructive characterisation wherever possible. This study reports on the use of luminescence, Raman and laser-induced breakdown spectroscopy to characterise the two most commonly found uranyl vanadates in nature, carnotite (K2 (UO2 )2 V2 O8 ·3H2 O) and tyuyamunite (Ca(UO2 )2 V2 O8 ·5–8H2 O); the first attempt to use all three laser-based techniques in tandem for these phases. Significant differences in the luminescence emission signal intensity along with a noticeable shift in the resolved emission peak positions enable carnotite and tyuyamunite to be readily distinguished. Extraction of the band spacing from luminescence emission spectra provides confirmation of the position of the equivalent Raman uranyl symmetric stretch, ν 1 (UO2 ) 2+, vibration for each mineral. Raman itself, was unable to differentiate carnotite and tyuyamunite owing to the weak signals obtained; however, the degree of splitting in the vanadate symmetric stretch, ν 1 (VO3 ) 3-, feature and, to a lesser extent, the position of the ν 1 (UO2 ) 2+ peak might be used to distinguish between tyuyamunite and metatyuyamunite, although further studies are required for confirmation. Compositional LIBS analysis was successful in identifying minor quartz, gypsum, Mg- and Fe-bearing inclusions, subsequently confirmed by optical and scanning electron microscopy. The findings indicate that multiple laser-based techniques offer the potential for real-time characterisation of uranyl vanadate phases where intrusive sampling, transportation and 'off-site' laboratory analysis is impracticable. Graphical abstract: Image 1 Highlights: Alternative in situ methods where intrusive sampling and analysis are impracticable. First in tandem characterisation using complementary Raman, luminescence and LIBS. First reported luminescence excitation and emission spectra for both minerals. Band spacing confirms the position of the equivalent Raman ν 1 (UO2 ) 2+ mode.